Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T17:36:19+01:00
A) 6-a+5-3a+a+a=-3a+15
6-a+a+3+6-3a=-3a+15
a+3+5-a+7-3a=-3a+15
6-3a+a+5+4-a=-3a+15
5-3a+5-a+a+5=-3a+15
a+4+7-3a+4-a=-3a+15
6-a+5-a+4-a=-3a+15
a-4+5-a+6-3a=-3a+15
odp.: Ten kwadrat jest kwadratem magicznym.

1. ( 2x - 1 ) + ( 4x - 2 ) + ( x + 1 ) = 2x - 1 + 4x -2 + x + 1 = 7x - 2
2. ( 4x - 2 ) + ( 2x + 1 ) + ( x - 1 ) = 4x - 2 + 2x + 1 + x - 1 + 7x - 2
3. ( x + 1 ) + ( 3x - 1 ) + ( 3x - 2 ) = x + 1 + 3x - 1 + 3x - 2 = 7x - 2
4. ( 2x - 1 ) + ( 2x - 2 ) + ( 3x + 1 ) = 2x - 1 + 2x - 2 + 3x + 1 = 7x - 2
5. ( 4x - 2 ) + ( 2x + 1 ) + ( x - 1 ) = 4x - 2 + 2x + 1 + x - 1 = 7x - 2
6. ( x + 1 ) + ( 3x - 1 ) + ( 3x - 2 ) = x + 1 + 3x - 1 + 3x - 2 = 7x - 2
7.( 2x - 1 ) + ( 2x + 1 ) + ( 3x - 2 ) = 2x - 1 + 2x + 1 + 3x - 2 = 7x - 2
8.( x + 1 ) + ( 2x + 1 ) + ( 3x + 1 ) = x + 1 + 2x + 1 + 3x + 1 = 6x + 3

Odpowiedź : Nie Jest Kwadrat Magiczny . !

Mam nadzieję że pomogłam licze na naj :)

1 2 1